Structural Transformation and the Kuznets Hypothesis: Evidence from ASEAN Countries - Sembiring, Eunike Novelia; Ahmad, Fahmi Salam (Universitas Negeri Gorontalo, 2026)
According to the Kuznets hypothesis, economic development initially leads to higher income inequality, which then tends to decline as structural transformation and factor mobility increase. This dynamic remains particularly relevant for emerging ASEAN economies that are currently undergoing rapid structural changes in their production and employment structures. This study aims to analyze the relationship between economic greenness, economic sector structure, and income inequality in ASEAN countries, namely Indonesia, Malaysia, Singapore and Thailand. The data used is time series data, with the period adjusted based on the availability of each country. The analysis method used is descriptive analysis and Autoregressive Distributed Lag (ARDL). The results show that Kuznets hypothesis is proven in Indonesia and Singapore. In addition, service sector share has a positive and significant influence on income inequality (Gini ratio) in Indonesia in the long run. However, the growing share of the service sector tends to raise inequality in Indonesia, suggesting that structural transformation which is not inclusively directed may widen income gaps despite economic growth.